Le lieu-dit des « Trois-Piliers » : un ensemble à caractère monumental du iiie s. apr. J.-C. dans la périphérie nord-est de Reims/Durocortorum ? - Philippe Rollet; Émilie Jouhet (Gallia)
The place known as “Trois-Piliers” is located on one of the lower elevations, overlooking the city of Reims. It occupies the border of the northeastern quarter of the Early Empire city, delimited a few dozen meters to the north by the Augustan enclosure and located 250 m east of the Reims (Marne)-Bavay (Nord) road. The excavation of 59 rue Belin in 1998-1999 demonstrated for the first time the presence of massive structures in this neighborhood, known since the 19th c. for its strong archaeological potential, but only through ancient sources. Carried out over an area of nearly 1,000 m2, this excavation uncovered a large semi-buried room, seemingly very similar to a cryptoporticus. Measuring at least 57 m long and 7.80 m wide, it is fitted with a series of pillars along its eastern wall and is bordered on the outside by a wide drain. The walls of the room, like those of the drain, possess similar technical characteristics, indicating the likelihood that they belong to the same phase of construction. The cladding is composed of small, very neat units, mounted in opus vittatum, with calibrated pyramidal shaped fragments of limestone. And while the cladding courses are perfectly horizontal, the internal blocking is composed of small limestone fragments, bound with a tile mortar. Built at the beginning of the 3rd c., this building was partially destroyed at the end of the second third of the 3rd c. by a fire. This in turn made it possible to identify all of the composing elements of its roof. The layer of destruction is essentially composed of ash, burned beams, metal elements and thousands of fragmented tiles. The tegulae and imbrices, calibrated but of small dimension, do not present any particularity and, as far as the timber roof truss is concerned, the numerous charred fragments retrieved are primarily oak (especially for the most important pieces), though some smaller elements were made of fir. The numerous nails and objects made of ferrous alloys collected, illustrate a wide range of hardware used by Gallo-Roman builders in roof construction. The low representation of large structural nails can be explained by a framework design centered on the use of triangulated trusses, for which the mortise and tenon joints of the crossbeams are held together by wooden pegs. The other metal elements (such as hangers), consisting of a hook and a riveted pin, suggest the presence of a suspended ceiling or false ceiling, likely made of wood, insofar as no other type of material (stucco or terracotta tiles, for example) were identified among the burned remains.